Assessing BI Maturity: Government Financial Sector Case Study - Sihotang, Jhon Rafles; Hidayanto, Achmad Nizar; Isal, Yugo Kartono (Jurnal Informatika Ekonomi Bisnis, 2025)
This study assesses the implementation maturity of a Business Intelligence system within a government organization in the Indonesian financial sector. The primary objectives are to evaluate the current maturity level and to formulate evidence-based recommendations for enhancement. The research employs a mixed-methods approach, utilizing the Business Intelligence Maturity Model as the analytical framework. Data was gathered from organizational documents, direct observation, a questionnaire survey of 13 system users, and in-depth interviews with four key stakeholders. The results indicate an overall BI maturity at Level 3: Information Integration. Despite this, five sub-dimensions scored poorly: Technical Data Management, Analysis Functionality in Applications, Reporting Capability in Applications, System Availability, and Profitability Calculation, signifying suboptimal implementation in these areas. The study concludes that the BI implementation is only partially successful and has not reached its intended potential. To advance to a higher maturity level, the organization must address the identified weaknesses, particularly in data management, application functionality, and system governance. This study offers practical guidance for organizational improvement and enriches limited academic literature on BI maturity in developing-country public financial institutions.